Feasibility Assessment of Patient Registry Research Using Clinical Data from Korean Medicine Arrhythmia Clinic - Hyeongyeong Lee; Youngju Oh; Sang-Song Shim; Hyeryun Lee; Dasol Park; Jungtae Leem (Journal of Korean Medicine, 2026)
Objectives: Evidence on the feasibility of arrhythmia registries in Korean medicine primary care is limited. Feasibility was assessed using a retrospective chart review.Methods: Adult records from an arrhythmia clinic at a single Korean medicine primary care clinic (February 2024–September 2025) were reviewed. Feasibility was assessed by patient recruitment, follow-up duration, visit and test frequency, and data availability, with k-means clustering for clinical characterization and random forest analyses to explore predictors of herb use.Results: Of 1,687 new visitors, 83 patients were included, with a mean enrollment of 4.2 ± 2.8 patients per month over 20 months. Baseline medical and social history exceeded 80% availability, while Electrocardiogram and heart rate variability were available in approximately 70%; auscultation, echocardiography, and laboratory data were rarely recorded. Among patients with follow-up, visits, tests, and treatments occurred at median intervals of 11–35 days with substantial variability. Three clinical clusters were identified, whereas random forest modeling was limited by data availability.Conclusions: This study supports the feasibility of arrhythmia registry research in Korean medicine primary care and informs future multicenter prospective registry design.